CURRENT STATE OF THE HEART VALVES POSTOPERATION MANAGEMENT - I. A. Gorlova; M. Yu. Omelchenko; T. I. Kazantseva; A. O. Nedoshivin; B. B. Bondarenko (Российский кардиологический журнал)
The article summarizes a long-term follow-up experience on the patients underwent various operation types on cardiac valves, specifics of individualized approach at outpatient stage, reach of optimal hypocoagulation taking recent guidelines, prevention and early diagnostics of prosthesis-related complications, as principals of management and necessity of extracardiac surgical interventions for the pregnant.